Genetic transformation strategies to address the major constraints to banana and plantain production in Africa: Technical manual of the training workshop on enhancing capacity for nematode management in small-scale banana cropping systems held at the Institute of Plant Breeding, University of the Philippines Los Baños Laguna, Philippines, 1-5 December 2003. - Atkinson, H.; Dale, J.; Harding, R.; Kiggundu, A.; Kunert, K.; Muchwezi, J.M.; Sagi, L.; Viljoen, Altus (2003)
This document was prepared for a workshop held in Kampala, Uganda, in August 2003. The objective of the workshop was to review the state-of-the-art of molecular and transformation technologies available for bananas as well as identify the strategies most likely to find field applications and make an impact on the livelihoods of smallholder farmers.